Impactul serviciilor de salubritate din România asupra condițiilor de habitat și a calității vieții - Studiu de caz: Municipiul București - Chiriac, Dumitru; Humă, Cristina (Calitatea Vieții, 2007)
Romania is currently confronted with an improper management of the wastes, particularly of the urban wastes, as shown, among other, by the unsatisfactory hygiene of most localities. Among them is Romania’s largest urban agglomeration – the Municipality of Bucharest, where pollution by wastes is especially visible by the garbage littered both in the streets and on the green areas or on the land not occupied by constructions. The paper presents the factors that influence the hygiene status of the city, how city cleaning is done, the perception of the population and the opinions of the different actors involved in the act of cleaning the city, the state of city cleanness. Also, the programs initiated by the environmental authorities, by the authorities of the local administration, by the service operators and by the nongovernmental organisations are presented, concerning, particularly, the education, stimulation, and making the population aware of the need to have a cleaner city.